ОЙЫНЛАРДЫ ОҚЫТЫЎ ҚУРАЛЫ СЫПАТЫНДА ҚОЛЛАНЫЎДЫҢ ПСИХОЛОГИЯЛЫҚ-ПЕДАГОГИКАЛЫҚ ТИЙКАРЛАРЫ - Жақсымуратова, Э.; Арысланбаева, А. (FAN va JAMIYAT, 2019)
The article contains the retrospective analysis of the literature about application of games in educational process it is proved that game as a means of training has received a wide recognition, and to the present time the didactical and psychological importance of games. The investigation of age and mental features of the child has shown, that the application of games in educational process corresponds to psychology of perception by the child of the environmental world.